2008
DOI: 10.1074/jbc.m802667200
|View full text |Cite
|
Sign up to set email alerts
|

Cdt1 and Cdc6 Are Destabilized by Rereplication-induced DNA Damage

Abstract: The replication factors Cdt1 and Cdc6 are essential for origin licensing, a prerequisite for DNA replication initiation. Mechanisms to ensure that metazoan origins initiate once per cell cycle include degradation of Cdt1 during S phase and inhibition of Cdt1 by the geminin protein. Geminin depletion or overexpression of Cdt1 or Cdc6 in human cells causes rereplication, a form of endogenous DNA damage. Rereplication induced by these manipulations is however uneven and incomplete, suggesting that one or more mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 44 publications
8
56
1
1
Order By: Relevance
“…S5F) and strongly induced re-replication ( Supplementary Fig. S5G), as previously reported 39 31.7% ΔPEST ( Supplementary Fig. S5G, see also Fig.…”
Section: Resultssupporting
confidence: 68%
“…S5F) and strongly induced re-replication ( Supplementary Fig. S5G), as previously reported 39 31.7% ΔPEST ( Supplementary Fig. S5G, see also Fig.…”
Section: Resultssupporting
confidence: 68%
“…2C). Furthermore the levels of Cdc6, which previously had been shown to decrease upon DNA damage (15,16), and of Cdc7 remained unchanged upon Geminin depletion (Fig. 2C).…”
Section: Significancementioning
confidence: 73%
“…However, it also has been suggested that Geminin actively inhibits Cdt1, because depletion of Geminin in G2 phase activates Cdt1 and causes DNA rereplication and, consequentially, DNA damage (12). Because Cdt1 and cell division cycle 6 (Cdc6) replication factors have been shown to be degraded after DNA damage (15)(16)(17)(18)(19), the Cdt1 decrease upon Geminin depletion simply may be an indirect consequence of DNA rereplication.…”
mentioning
confidence: 99%
“…Flow cytometry analysis was performed using a Cyan FACScan (DakoCytomation) and Summit version 4.3 software (DakoCytomation) as described previously (36).…”
Section: Methodsmentioning
confidence: 99%